Adjunctive Micronutrient Therapy in Sepsis: Associations with Inflammation and Organ Dysfunction - Prima , Agus; Lubis , Bastian (Journal of Society Medicine, 2026)
Introduction: Despite advances in supportive care, sepsis remains a major cause of morbidity and mortality among critically ill patients. Adjunctive therapies targeting inflammation and endothelial dysfunction, such as thiamine and ascorbic acid, have gained increasing attention in recent years. Matrix metalloproteinase-9 (MMP-9) and its inhibitor TIMP-1 are key biomarkers involved in inflammatory dysregulation and organ dysfunction in sepsis. Methods: This retrospective cohort study was conducted over 12 months at Haji Adam Malik General Hospital. A total of 147 adult patients with sepsis were initially enrolled and categorized into four groups: normal saline (control), thiamine, ascorbic acid, and thiamine–ascorbic acid combination therapy. Propensity score matching was applied to achieve comparable baseline characteristics, resulting in 25 patients in each group. Serum MMP-9 and TIMP-1 levels were measured at the Integrated Laboratory, Faculty of Medicine, Universitas Sumatera Utara. The clinical outcomes included incidence rates, MMP-9/TIMP-1 ratios, and Sequential Organ Failure Assessment (SOFA) scores. Results: Combination therapy did not significantly reduce the incidence rate (OR 1.19; 95% CI 0.37–3.80) or MMP-9/TIMP-1 ratio (OR 0.34; 95% CI 0.09–1.30) compared to the control. In contrast, a single administration of ascorbic acid and thiamine significantly reduced the incidence rates and improved the MMP-9/TIMP-1 balance. Combination therapy was not associated with improved SOFA scores (OR 2.66; 95% CI 0.85–8.36). Conclusion: Combined thiamine and ascorbic acid therapies did not confer any superior clinical or biomarker benefits. Single-agent thiamine or ascorbic acid therapy demonstrated favorable effects on the incidence rate, MMP-9/TIMP-1 ratio, and organ dysfunction in patients with sepsis.